2023
DOI: 10.1002/jnr.25225
|View full text |Cite
|
Sign up to set email alerts
|

ER‐phagy in neurodegeneration

Abstract: There are many cellular mechanisms implicated in the initiation and progression of neurodegenerative disorders. However, age and the accumulation of unwanted cellular products are a common theme underlying many neurodegenerative diseases including Alzheimer's disease, Parkinson's disease, and Niemann–Pick type C. Autophagy has been studied extensively in these diseases and various genetic risk factors have implicated disruption in autophagy homoeostasis as a major pathogenic mechanism. Autophagy is essential i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 142 publications
0
3
0
Order By: Relevance
“…Among interactions of a group of proteins not mapped by the aforementioned pathway analysis in the TF-HaloMS dataset ( P > .001, Supplementary Fig. S4 and Supplementary Table S16 ), we found a novel subnetwork of proteins involved in ER-phagy, neurodegenerative disease [ 93 ], ER-phagy, neurodegenerative disease, and myelodysplastic and master regulators in adipocytes ( Supplementary Fig. S10D and Supplementary Table S33 ).…”
Section: Resultsmentioning
confidence: 99%
“…Among interactions of a group of proteins not mapped by the aforementioned pathway analysis in the TF-HaloMS dataset ( P > .001, Supplementary Fig. S4 and Supplementary Table S16 ), we found a novel subnetwork of proteins involved in ER-phagy, neurodegenerative disease [ 93 ], ER-phagy, neurodegenerative disease, and myelodysplastic and master regulators in adipocytes ( Supplementary Fig. S10D and Supplementary Table S33 ).…”
Section: Resultsmentioning
confidence: 99%
“…Disorders of ER structure and function have also been identified in AD, PD, and prion diseases. On top of this, abnormalities of ER-phagy or RE degradation by lysosomes have been observed in AD, PD, Niemann–Pick type C, and schizophrenia [ 12 , 53 ]. Gupta and his team also identified large changes in the expression of genes encoding nuclear transcription factors by analyzing data from 300,000 patients with 30 different diseases of aging [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Neurons are particularly susceptible to accumulating unwanted cellular products, so proper regulation of the autophagy process is crucial. Indeed, it has been reported that alterations in autophagy may be associated with neurodegenerative diseases such as Alzheimer's, Parkinson's, and NPC [53]. As already known, the liver and CNS are among the organs most affected by NPC diseases.…”
Section: Autophagy In Npcmentioning
confidence: 96%